Consolidation Therapy in Ovarian Cancer: A Clinical Update. (1st November 2009) - Sabbatini, Paul
Abstract : Objectives: To evaluate current strategies under investigation for use as consolidation or maintenance treatment in patients with ovarian cancer. Patients with epithelial ovarian cancer often enter a complete remission after primary treatment. Many relapse, unfortunately, but some can return to remission after additional treatment. Outcomes can be improved by applying effective consolidation or maintenance approaches to patients in a complete primary or subsequent remission. Methods: A selective review of the literature is undertaken to consider strategies that are being or will likely be evaluated in randomized trials while we assess whether consolidation or maintenance will have a place in the treatment of patients with ovarian cancer. Results: The application of extended standard cytotoxic agents has been generally disappointing, and no strategy applied in the first remission setting has prolonged overall survival. Conclusions: As treatment options move beyond classic chemotherapy to novel hormones, immune interventions, and biologic agents, the consolidation strategy is regaining interest. This is particularly attractive in that many of these agents have stable disease as best outcome, and this is most appropriate to evaluate in patients with minimal volume disease. A consideration of toxicity is paramount, and any strategy to be considered in an otherwise asymptomatic patient in remission must be well tolerated. In addition, patients in second or third complete remission are also being considered as an appropriate group in which to evaluate new agents. Numerous other phase 2 trials with novel agents not considered here are underway, and it is to be hoped that some will emerge as contenders for randomized trials. Participation in these trials remains a priority for patients who otherwise must pursue a difficult watch-and-wait strategy.